Does Cultural Diversity of Board of Directors Affect Corporate Environmental Performance? Evidence From the Energy Sector - Varrone, Nicola; D’Angelo, Eugenio; Gangi, Francesco; Daniele, Lucia Michela (European Scientific Journal, ESJ, 2020)
This paper has a twofold objective. First, it intends to investigate if and how the cultural diversity of the board of directors affects the corporate environmental performance of energy firms. Second, it aims at verifying if the relationship between board cultural diversity and corporate environmental performance varies across different legal systems. To address this topic, panel data methodology was used on a sample of 153 firms operating in the energy sector, from 32 countries, over the period 2013-2018. The findings suggest that a higher board’s cultural heterogeneity positively affects corporate environmental performance. Moreover, the study reveals that this link is stronger among energy firms from civil law countries compared to energy firms from common law countries.